Exercise training in intermittent claudication: Effects on antioxidant genes, inflammatory mediators and proangiogenic progenitor cells - Nowak, Witold N.; Mika, Piotr; Nowobilski, Roman; Kusinska, Katarzyna; Bukowska-Strakova, Karolina; Nizankowski, Rafal; Jozkowicz, Alicja; Szczeklik, Andrzej; Dulak, Jozef (Thrombosis and Haemostasis, 2012)
Exercise training remains a therapy of choice in intermittent claudication (IC). However, too exhaustive exercise may cause ischaemic injury and inflammatory response. We tested the impact of three-month treadmill training and single treadmill exercise on antioxidant gene expressions, cytokine concentrations and number of marrow-derived proangiogenic progenitor cells (PPC) in the blood of IC patients. Blood samples of 12 patients were collected before and after training, before and 1, 3 and 6 hours after the single exercise. PPCs were analysed with flow cytometry, cytokine concentrations were checked with Milliplex MAP, while expression of mRNAs and miRNAs was evaluated with qRT-PCR. Treadmill training improved pain-free walking time (from 144 ± 44 seconds [s] to 311 ± 134 s, p=0.02) and maximum walking time (from 578 ± 293 s to 859 ± 423 s, p=0.01) in IC patients. Before, but not after training, the single treadmill exercise increased the number of circulating CD45dimCD34+CD133-KDR+ PPCs (p=0.048), decreased expression of HMOX1 (p=0.04) in circulating leukocytes, reduced tumour necrosis factor-α (p=0.03) and tended to elevate myeloperoxidase (p=0.06) concentrations in plasma. In contrast, total plasminogen activator inhibitor-1 was decreased by single exercise only after, but not before training (p=0.02). Both before and after training the single exercise decreased monocyte chemoattractant protein (MCP)-1 (p=0.006 and p=0.03) concentration and increased SOD1 (p=0.001 and p=0.01) expression. Patients after training had also less interleukin-6 (p=0.03), but more MCP-1 (p=0.04) in the blood. In conclusion, treadmill training improves walking performance of IC patients, attenuates the single exercise-induced changes in gene expressions or PPC mobilisation, but may also lead to higher production of some proinflammatory cytokines.
Keywords: Ischaemia; oxidative stress; inflammation; microRNA; heme oxygenase-1